Defining the Logical Boundary of a Service: An Improved Model and Novel Metrics for Service-Oriented Systems - Singh, Rupinder Pal; Singh, Hardeep (INFOCOMP Journal of Computer Science, 2020)
In the field of service-oriented systems, a service is considered as an artifact that has a logical representation. However, the logical boundary of a service is not clearly defined. In particular, it needs to be defined clearly at the design level. Without such a definition, it is not possible to delineate incoming and outgoing coupling of a service. It would be difficult to analyze overall static, inter-modular coupling of a service. Further, one cannot devise effective metrics for design characteristics like complexity, cohesion and coupling of a service. A definition that is both technology-agnostic and independent of the physical packaging of a service would be most suitable. This paper defines the logical boundary of a service, improves a generic formal model and defines new metrics.